OBSERVATIONS ON'THE OCCURRENCE OF PENAEID POSTLARVAE IN KORAPUZHA ESTUARY - Menon, K Koumudi (Indian Journal of Fisheries, 2011)
The pattern 0If postlarval occurrence studied during 1973-75 in Korapuzhaestuary near Calicut indicated that M. dobsoni and P. indicus are more or less continuousbreeders, whereas, the spawning of M. monoceros seems to take placemainly ,in the summer months. M. dobsoni has spa,wning pe,aks during ,the monsoonand post-mo:!soon pe,riO'd whe'reas the principal peak for P. indicus is in summe,ror pre-monsoon months. It has lbeen ohse,pved that P. indicus and M. monocerosoccurred mainly in the periods of high saline conditions wh:ITe M. dobsoni showeda tendency to occur more dur,ing the period wile:! the water was less saline.